PERTANGGUNGJAWABAN PPAT YANG MELAKUKAN PEMALSUAN TANDA TANGAN AKTA JUAL BELI (Studi Kasus Putusan Nomor 412/PDT/2018/PT DKI) - Khanza Inas Az-Zahra Fikry; Shinta Andriyani (Fakultas Hukum Universitas Mataram, 2021)
This study aims to determine the validity of the sale and purchase deed that has juridical defects,the legal sanctions against PPAT for falsifying the sale and purchase deed signed,the basis and consideration of the judge in adjudicating the case in decision Number 412/PDT/2018/PT DKI.Type of research is normative legal research using a statute approach, a case approach, and a conceptual approach. The results of the research, the sale and purchase deed he made was null and void, the legal sanctions given were paying material losses and paying court fees, the basis and consideration of the judge were false evidence, Law Number 1 of 1974,and the Civil Code.